A model to incorporate genetic testing (5-HTTLPR) in pharmacological treatment of major depressive disorders - Serretti, Alessandro; Olgiati, Paolo; Bajo, Emanuele; Bigelli, Marco; De Ronchi, Diana (The world journal of biological psychiatry, 2011)
Abstract Objective. To evaluate the benefit of pharmacogenetics in antidepressant treatment. Methods. In a simulated trial 100,000 subjects in a current episode of major depressive disorder (MDD) received citalopram or bupropion based on the clinician's decision (algorithm A) or following indications from 5-HTTLPR genetic testing (algorithm B), which effect size of was estimated from a meta-analysis of pharmacogenetic trials. A and B were compared in a cost-utility analysis (12 weeks). Costs (international $, 2010) were drawn from official sources. Treatment effects were expressed as quality-adjusted life weeks (QALWs). Outcome was incremental cost-effectiveness ratio (ICER). Results. Under base-case conditions, genetic test use was associated with increases in antidepressant response (0.062 QALWs) and tolerability (0.016 QALWs) but cost benefit was not acceptable (ICER = $2,890; $1,800-$4,091). However, when the joint effect on antidepressant response and tolerability was analyzed in two recurrent episodes, ICER dropped to $1,392 ($837-$1,982). Cost-effectiveness acceptability curve (CEAC) showed a >80% probability that ICER value fell below the commonly accepted 3 times Gross Domestic Product (GDP) threshold (World Health Organization) and therefore suggesting cost-effectiveness. Conclusion. Notwithstanding some caveats (exclusion of gene-gene and gene-environment interactions; simple 5-HTTLPR architecture), this simulation is favourable to incorporate pharmacogenetic test in antidepressant treatment.